Cutting Bread or Cutting Throats? – Findings from a New Database on Religion, Violence and Peace in Sub-Saharan Africa, 1990 to 2008 - Matthias Basedau; Georg Strüver; Johannes Vüllers (German Institute of Global and Area Studies (GIGA), 2011)
Despite the religious diversity in sub-Saharan Africa and the religious overtones in a number of African conflicts, social science research has inadequately addressed the question of how and to what extent religion matters for conflict in Africa. This paper presents an innovative data inventory on religion and violent conflict in all sub-Saharan countries for the period 1990-2008 that seeks to contribute to filling the gap. The data underscore that religion has to be accounted for in conflict in Africa. Moreover, results show the multidimensionality (e.g. armed conflicts with religious incompatibilities, several forms of non-state religious violence) and ambivalence (inter-religious networks, religious peace initiatives) of religion vis-à-vis violence. In 22 of the 48 sub-Saharan countries, religion plays a substantial role in violence, and six countries in particular-Chad, Congo-Brazzaville, Ethiopia, Nigeria, Sudan and Uganda - are heavily affected by different religious aspects of violence. – – Bislang haben - trotz der religiösen Vielfalt und religiös motivierter Auseinandersetzungen in Afrika - nur wenige Studien den Zusammenhang von Religion und Konflikt in Subsahara-Afrika systematisch untersucht. Insbesondere mangelt es an Untersuchungen, die den Einfluss von Religion in den Mittelpunkt stellen und die Stärke und Art der Beeinflussung von Konflikten durch Religion in Afrika analysieren. Der vorliegende Artikel soll diese Forschungslücke mit Hilfe der systematischen Auswertung einer neuen Datenbank zu Religion in Subsahara-Afrika (RSSA) für den Zeitraum von 1990 bis 2008 schließen. Die Ergebnisse zeigen, dass religiös motivierte Konflikte in Afrika zahlreicher sind als oftmals angenommen. Ferner unterstreichen die Ergebnisse die Multidimensionalität (z.B. Gewaltkonflikte mit theologischen Gegensätzen, weitere Typen nicht-staatlicher religiöser Gewalt) und die Ambivalenz (z.B. interreligiöse Netzwerke, religiöse Friedensinitiativen) von Religion. Insgesamt spielt Religion in 22 der 48 Länder Subsahara-Afrikas eine bedeutsame Rolle bei gewaltsamen Auseinandersetzungen. Sechs Länder - (Äthiopien, Kongo-Brazzaville, Nigeria, Sudan, Tschad und Uganda) - sind besonders stark von unterschiedlichen religiösen Gewaltfaktoren betroffen.
Keywords: 300; religion; sub-Saharan Africa; violence; peace; conflict; Religion; Politischer Konflikt; Politische Unruhen; Afrika südlich der Sahara